EFEKTIVITAS PENGGUNAAN METODE STRUKTURAL ANALITIK SINTETIK TERHADAP KEMAMPUAN LITERASI PESERTA DIDIK KELAS II - Galib, Nur; Halimah, Andi; Rosdiana, Rosdiana; Fatahullah, M (Jurnal Ilmiah Pendidikan Madrasah Ibtidaiyah, 2022)
This study is a pre-eksperimental design study that aims: 1) To determine the literacy ability of students before using the synthetic analytical structural method in class II SDN 154 Sekkang Soppeng Regency, 2) To determine the literacy ability of students after using the synthetic analytical structural method in class II SDN 154 Sekkang Soppeng Regency and 3) To determine the effectiveness of the use of synthetic analytical structural methods on the literacy skills of second grade students at SDN 154 Sekkang Soppeng Regency. Sampling was carried out using the saturated sample technique so that the number of samples obtained was 12 students. The research instrument used was a literacy test sheet, namely reading. The data analysis used in this study was descriptive and inferential statistical analysis techniques with the help of the SPSS 20 application. Based on the results of literacy skills before and after using the synthetic analytical structuralThis study is a pre-eksperimental design study that aims: 1) To determine the literacy ability of students before using the synthetic analytical structural method in class II SDN 154 Sekkang Soppeng Regency, 2) To determine the literacy ability of students after using the synthetic analytical structural method in class II SDN 154 Sekkang Soppeng Regency and 3) To determine the effectiveness of the use of synthetic analytical structural methods on the literacy skills of second grade students at SDN 154 Sekkang Soppeng Regency. Sampling was carried out using the saturated sample technique so that the number of samples obtained was 12 students. The research instrument used was a literacy test sheet, namely reading. The data analysis used in this study was descriptive and inferential statistical analysis techniques with the help of the SPSS 20 application. Based on the results of literacy skills before and after using the synthetic analytical structural method there were differences, namely before using the synthetic analytical structural method with the highest score of 60 and the lowest 40 with an average the average is 47.08, while after using the synthetic structure analysis method the highest value is 83 and the lowest is 60 so that the average is 73.42. This can be seen in the t-test analysis that has been carried out using a paired sample ttest with the help of SPSS 20 which shows Thit = 14,189 with Ttable = 2,262. So it can be concluded that the synthetic analytic structural method is effective on the literacy skills of second grade students at SDN 154 Sekkang Soppeng Regency. method there were differences, namely before using the synthetic analytical structural method with the highest score of 60 and the lowest 40 with an average the average is 47.08, while after using the synthetic structure analysis method the highest value is 83 and the lowest is 60 so that the average is 73.42. This can be seen in the t-test analysis that has been carried out using a paired sample ttest with the help of SPSS 20 which shows Thit = 14,189 with Ttable = 2,262. So it can be concluded that the synthetic analytic structural method is effective on the literacy skills of second grade students at SDN 154 Sekkang Soppeng Regency.